AN ILLUSTRATION BOOK OF NOODLE-BASED CULINARY RESTAURANTS IN SOUTH JAKARTA - Nariswari, Gandes Dahayu; Nurbani, Sri; Aditya, Dimas Krisna (eProceedings of Art & Design, 2024)
South Jakarta is a city that moves in a fast pace in accordance to trends and development which contributed to the rise of their economy which is seen in the impact of the business as well. Jakarta is known for their large agglomeration due to its impact from immigration of new settlers coming from different areas which shaped economic conditions to the maximum potential. (Waworoentoe, 2019) The entrance of noodle culture in Indonesia is caused by the acculturation happening between the people of China with Indonesian locals which resulted in fusion of food, and that9s how the term 8Mie9 was localized. (Sunuantari et al., 2019). The idea of this research is to create an exploration guide around South Jakarta using noodle restaurants embarking target audience on a journey to lift up 8worth-trying9 noodle business. Inspired by the work of Tirta Lie9s <Tirta Lie 100+ Bakmi Terlezat Di Jakarta= (2019) the design of the book will include complete guidance about noodle places in regards to their ambience, price range, type of noodles, operating hours and most importantly contacts available to reach out to business owners. The outcome of this project is needed based on several reasons: (1) For readers to be able to explore noodle restaurants around South Jakarta, (2) Communicating design results through visualized diagram, and (3) To uplift (spread awareness about) noodle business by using a promotional method that is available through informative media. An illustrative guidebook is a solution to the points mentioned above as it generates visual in forms of illustration that could be translated by the artist as a communication tool for the readers. To strengthen this research the author collects data in various forms such as literature studies, questionnaires and observations and will be adapting qualitative method for the purpose of quality control in finding the most delicious bowl of noodles eligible for target audience to taste. Keywords: informative media, visual communication design, illustration, noodles, culinary, culture, awareness.